Post-Disaster Trauma Recovery for Children Through Didong Gayo Play Therapy Based on Local Wisdom - Wajnah W (Madani: Jurnal Ilmiah Multidisiplin, 2026)
Natural disasters are events that have multidimensional impacts on people’s lives. In addition to causing physical damage, economic losses, and disruption of social activities, disasters also give rise to serious psychological problems, especially for children. Children who experience disaster situations often face severe emotional stress due to their limited ability to understand and control the events they experience. The resulting psychological trauma may include prolonged fear, anxiety, sleep disorders, behavioral changes, decreased social interaction skills, and loss of a sense of security in daily life. If these conditions are not handled properly, they may affect children’s emotional, social, and educational development in the long term. This study aims to examine the effectiveness of Didong Gayo play therapy based on local wisdom as a medium for trauma recovery among children after disasters. The research employed a descriptive qualitative approach with data collection techniques consisting of observation, in-depth interviews, and documentation. The results showed that Didong Gayo play therapy was able to help children express emotions, reduce anxiety, increase their sense of security, and improve social relationships among children. Local cultural elements contained in Didong Gayo, such as music, poetry, rhythmic movements, and togetherness, had a positive influence on children’s psychological conditions. A local wisdom-based approach was also proven to be more easily accepted by the community because it aligns with local culture and social values